Pengaruh Problem Based Learning dan Motivasi terhadap Minat Belajar Siswa pada Materi Bangun Ruang - Khoiriyah, Ummi Mammlaul; Faizah, Siti (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
Motivation and interest in learning are important in influencing student learning achievement. This research aims to determine whether there is or not; (1) the influence of the Problem Based Learning model on students' interest in learning (2) the influence of learning motivation on students' interest in learning, and (3) the influence of the Problem Based Learning model and learning motivation on students' interest in learning in Building Materials. This research design uses a one-shot case study design. This research involved 32 of VII grade. The research instruments used included tests, motivation questionnaires and students' interest in learning. The data obtained was analyzed using inferential statistics. The research results show that; (1) there is an influence on the problem-based learning model on students' interest in learning in spatial material, (2) there is no influence on student learning motivation on student's interest in learning in spatial material, and (3) based on the results of partial regression testing it is found that there is the influence of the problem based learning model and learning motivation on students' interest in learning about spatial building material.